2018
DOI: 10.1158/1078-0432.ccr-17-2619
|View full text |Cite
|
Sign up to set email alerts
|

HSP27-Mediated Extracellular and Intracellular Signaling Pathways Synergistically Confer Chemoresistance in Squamous Cell Carcinoma of Tongue

Abstract: Purpose: Squamous cell carcinoma of tongue (SCCT) is the most common type of oral cavity carcinoma. Chemoresistance in SCCT is common, and the underlying mechanism remains largely unknown. We aimed to identify key molecules and signaling pathways mediating chemoresistance in SCCT. Experimental Design: Using a proteomic approach, we found that the HSP27 was a potential mediator for chemoresistance in SCCT cells. To further validate this role of HSP27, we performed various mechanistic studies usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 25 publications
(23 reference statements)
1
36
0
Order By: Relevance
“…These data are supported by a pulmonary inflammation model wherein MK2 knockout mice had significantly lower levels of TNF-α and decreased phosphorylated HSP27 (p-HSP27) and NF-κb pathway signaling [46]. Additionally, Zheng and colleagues [47] showed increased HSP27 and IL-6 in chemoresistant squamous tongue carcinoma cells. This increased HSP27 expression activated NF-κb signaling, and led to increased tumor growth in vivo, and high HSP27 levels were correlated with worse overall survival in human patients [47].…”
Section: Discussionmentioning
confidence: 82%
“…These data are supported by a pulmonary inflammation model wherein MK2 knockout mice had significantly lower levels of TNF-α and decreased phosphorylated HSP27 (p-HSP27) and NF-κb pathway signaling [46]. Additionally, Zheng and colleagues [47] showed increased HSP27 and IL-6 in chemoresistant squamous tongue carcinoma cells. This increased HSP27 expression activated NF-κb signaling, and led to increased tumor growth in vivo, and high HSP27 levels were correlated with worse overall survival in human patients [47].…”
Section: Discussionmentioning
confidence: 82%
“…It was observed that an increase of Hsp27 levels is transiently induced at specific stages during development and cell differentiation and occurs concomitantly with the differentiation-associated decrease of cellular proliferation [28,29]. Other studies reported that Hsp27 is augmented in different types of tumors and its levels are directly associated with a more aggressive malignant behavior (cancer cell proliferation, invasiveness, and metastasis) and resistance to chemotherapy [30,31]. Furthermore, Hsp27 mediates endothelial cell mobility, improving angiogenesis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma of tongue Induction of multidrug-resistance by hyperactivating NF-κB signal and suppressing mitochondrial caspase signal Reduction of chemoresistance via HSP27 knockdown and its antibody treatment [95] Ovarian cancer Induction of cisplatin resistance by inhibiting p21 via activation of AKT pathway [96] Laryngeal cancer cell Induction of chemoresistance to cisplatin and staurosporin by delaying cell growth and remodeling actin polymerization [97] Pancreatic cancer Induction of chemoresistance to gemcitabine by activation of Snail and ERCC1 and decrease of E-cadherin [98] Lung cancer…”
Section: Hsp27mentioning
confidence: 99%
“…HSP27 enhances multidrug-resistance in squamous cell carcinoma of tongue (SCCT) through hyperactivation of NF-κB. [95]. In ovarian cancer, the increased expression of HSP27 induces cellular resistance against cisplatin therapy by inhibiting p21 transfer from the nucleus [96].…”
Section: Hsp40mentioning
confidence: 99%